1124 Levosimendan Rescue Therapy in Non-Cardiosurgical Neonates with Heart Failure: a Case Series. (October 2012) - Tempera, A; Piastra, M; Luca, E; Rosa, G De; Buffone, E; Conti, G; Carolis, MP De
Abstract : Background and Aims: To report the successful use of the new inodilator levosimendan in 4 critically ill neonates with refractory heart failure. At present, no data are available on the use of levosimendan in newborns outside the cardiosurgical setting. Methods: Clinical chart review. Results: Neonates described in Table 1 were given LS due to severe refractory heart failure when standard treatment was ineffective and/or complications occurred. LS was administered as a continuous i.v. infusion (0.2 mcg/kg/min over the first 24 hrs). LS addition resulted in an improvement and/or stabilisation of hemodynamic status, with nearly normal restoration of heart function in 2/4 infants. Patients with PH and RV enlargement could be weaned off from pulmonary vasodilators. Conclusions: In these full-term neonates with post-ischaemic low cardiac output/pulmonary hypertension and heart failure of infectious or metabolic origin, refractory to first line inotropic drugs, LS was a potent inotropic agent and a possible add-on therapy. As suggested, in the neonatal period LS may represent an ideal drug for immature myocardium characterized by a much more calcium dependent contractility than adults. Further studies are needed to evaluate the role of LS in refractory HF.